Febuxostat In Hyperuricemic Heart Failure: A Systematic Review of Cardiovascular Outcomes and Safety - Warham Warham; Jonea Octavien Wijaya; Willy Valerian Soumokil; Nur Islamy; Nurul Afiah Sudarianto (International Journal of Health and Pharmaceutical (IJHP), 2025)
Introduction: Hyperuricemia is highly prevalent in patients with heart failure (HF) and is associated with poor prognosis. Febuxostat, a selective non-purine xanthine oxidase inhibitor, provides potent urate-lowering effects and may reduce oxidative stress, but its cardiovascular safety in HF populations remains uncertain. Objective: To systematically review the evidence on febuxostat use in patients with hyperuricemia and heart failure, focusing on cardiovascular outcomes, safety, and mechanistic effects. Methods: This review was conducted according to PRISMA guidelines. Comprehensive searches of PubMed, Cochrane Library, and ScienceDirect up to September 2025 identified studies evaluating febuxostat in hyperuricemic HF patients. Eligible designs included randomized controlled trials, post hoc analyses, and observational cohorts. Data were extracted on study characteristics, interventions, comparators, outcomes, and risk of bias. Results: From 247 records screened, eight studies were included in the qualitative synthesis. Febuxostat consistently reduced serum uric acid levels and improved oxidative stress markers and diastolic function indices. Clinical outcome data were heterogeneous: while one large trial reported increased cardiovascular mortality, another demonstrated non-inferiority without excess risk. Subgroup and observational data suggested that HFpEF patients may benefit from febuxostat in terms of reduced hospitalization and mortality, whereas evidence in HFrEF was inconclusive. Risk of bias was generally low in randomized trials but higher in observational studies. Discussion: The findings highlight febuxostat’s mechanistic plausibility and potential phenotype-specific benefits, particularly in HFpEF. However, conflicting mortality signals from pivotal trials necessitate cautious interpretation. Limitations include small sample sizes in HF-focused studies, heterogeneity in patient populations, and limited long-term outcome data. Conclusion: Febuxostat is a potent urate-lowering therapy with mechanistic benefits in hyperuricemic HF, but evidence on clinical outcomes remains inconsistent. Selective use in carefully chosen HFpEF patients may be considered, pending further large randomized trials to clarify safety and efficacy.